Polymorphisms in the Promoter Region of Catalase Gene and Essential Hypertension. Issue 1 (9th June 2013) - Zhou, Xiao Feng; Cui, Jing; DeStefano, Anita L.; Chazaro, Irmarie; Farrer, Lindsay A.; Manolis, Athanasios J.; Gavras, Haralambos; Baldwin, Clinton T.
Abstract : Genetic variations that predispose individuals to complex disorders, such as essential hypertension, may be found in gene coding regions, intronic regions or in gene promoter regions. Most studies have focused on gene variations that result in amino acid substitutions because they result in different isoforms of the protein, presumably resulting in differences in protein properties. Less attention has been placed on the role of intronic or promoter mutations. In this report, we examined two single nucleotide polymorphisms (SNPs) in the catalase (CAT) gene prompter region in a cohort of hypertensive Caucasians and African Americans with a Mass Spec based Homogenous MassEXTEND assay. We found an association when a specific combination of the two promoter SNPs was examined in Caucasians. No association was observed in African Americans. Our data suggest that genetic variations in the promoter region of catalase gene influence the susceptibility to essential hypertension. In addition, the genetic factors that contribute to hypertension maybe different between ethnic groups.